Application of the Kirkpatrick 4-Level Evaluation Model in Learning Cultural Arts (dance) at Xavier Catholic High School During the Covid-19 Pandemic - Sri Sinta Lufianti Bago; Fuji Astuti (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This research aims to assess and describe the application of the Kirkpatrick 4-level evaluation model in learning cultural arts (dance) at Xaverius Catholic High School Padang during the COVID-19 pandemic. This type of research is an experimental study using the Kirkpatrick 4-level evaluation model. The population in this study were all XII grade students at Xaverius Catholic High School Padang, totaling 36 students. The data instrument used in this research is a questionnaire. This study uses the Kirkpatrick 4-Level Evaluation Model, in which each level has a way or technique for data collection. The data were analyzed using the percentage formula. The results of Level 1 research reaction with a questionnaire instrument with the acquisition of the average experimental class XII-IS (88.75) very good/satisfying category and the XII-MIA control class (85) very good/satisfying category Level 2 Learning: The results of the pre-test carried out by the experimental class XII-IS (72.25) category are quite good; the control class XII-MIA (76.25) category is good. Level 3 Attitude / Behavior (Behaviour) Experimental class XII-IS (62.5) good category, control class XII-MIA (92.5) very good category. Level 4 results: psychomotor skills owned by students from the experimental class XII-IS (76.87) are in the good category; control class XII-MIA (90.93) is in the very good category.